Academic trip to Kuala Lumpur - Kueh, Dorothy Chiok Choo (UiTM Sarawak, 2016)
As a fulfillment for the course, Issues and Ethics in Finance (FIN657), 36 BM242 Bachelor in Finance Part 5 students made a trip to Kuala Lumpur from 9 to 11 November 2015, accompanied by their lecturer. Madam Dorothy Kueh The trip was well organised with visits to institutions such as Cagamas Bhd, Lembaga Hasil Dalam Negeri (LHDN) Malaysia and Bank Negara which are relevant to the course.